Synthesis and Explosion Properties of Porous Silicon/Gadolinium Nitrate Energetic Composite - Wen, J.; Huang, H.; Li, X.; Tao, C.; Li, W. (Asian Journal of Chemistry, 2012)
In this paper, fresh porous silicon was prepared by electrochemical anodization method using a mixture of hydrofluoric acid and dinethylformamide as electrolyte. The obtained pores were loaded with Gd(NO3)3·6H2O oxidizer to create energetic material. Effect of the HF concentration on explosion properties was investigated by measurement of sound intensity and emission spectra of the explosion. The result shows that the optimal explosion property of the energetic material can be obtained when HF concentration is 31.4 wt % and the maximum colour temperature of the explosion reaches to 3495.1 K. Interaction between Si-Hx (x = 1, 2, 3) and Gd(NO3)3 in the energetic material was studied by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. A detailed demonstration for this interaction is presented.